2021
DOI: 10.3389/fphar.2021.682065
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Novel Serine Protease Inhibitor on Inflammation and Intestinal Permeability in a Murine Colitis Transfer Model

Abstract: Background: A protease/antiprotease disbalance is observed in inflammatory bowel diseases (IBD). We therefore studied the effect of the novel serine protease inhibitor UAMC-00050 on intestinal inflammation and permeability in a chronic colitis T cell transfer mouse model to get further insight into the regulation of T cell-mediated immunopathology.Methods: Colitis was induced in severe combined immunodeficient (SCID) mice, by the adoptive transfer of CD4+CD25−CD62L+ T cells. Animals were treated intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…The explanation for this increase is not entirely clear but might be explained by 1) the disturbance of the protease–anti-protease balance interfering with inflammatory or anti-inflammatory mediators, 2) an interaction with other luminal components (e.g., the microbiome or its metabolites), or 3) the presence of neutrophil extracellular traps, which could release proteins such as MPO but also neutrophil elastase or cathepsin G ( Drury et al, 2021 ; Hanning et al, 2021 ). Interestingly, we recently demonstrated an amelioration of the inflammatory parameters after a 2-week i. p. treatment with UAMC-00050 in a chronic colitis T cell transfer mouse model ( Van Spaendonk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this increase is not entirely clear but might be explained by 1) the disturbance of the protease–anti-protease balance interfering with inflammatory or anti-inflammatory mediators, 2) an interaction with other luminal components (e.g., the microbiome or its metabolites), or 3) the presence of neutrophil extracellular traps, which could release proteins such as MPO but also neutrophil elastase or cathepsin G ( Drury et al, 2021 ; Hanning et al, 2021 ). Interestingly, we recently demonstrated an amelioration of the inflammatory parameters after a 2-week i. p. treatment with UAMC-00050 in a chronic colitis T cell transfer mouse model ( Van Spaendonk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Van Spaendonk et al. (2021) induced chronic colitis by injecting 100 μL of 1 × 10 6 CD4 + CD25 − CD62L + T cells intraperitoneally into severe combined immunodeficient mice. The symptoms observed included weight loss and an elevated level of pro‐inflammatory cytokines.…”
Section: Adoptive Transfer Model Of Ibdmentioning
confidence: 99%
“…This is because of the high proteolytic activity observed in IBS patients [ 71 ]—the use of anti-proteases to counteract this activity takes relevance. Anti-protease of chemical origin [ 72 ] can be used, as well as bacteria that naturally expresses them. Motta et al [ 73 ] demonstrated the efficacy of a recombinant L. lactis strain expressing human elafin anti-protease activity against inflammation in a mouse model of IBD, with similar protection properties to those of IL-10, also delivered by a recombinant L. lactis strain.…”
Section: Target Screening To Select Bacterial Strains With Probiotic ...mentioning
confidence: 99%